LEARNERS’ PERCEPTION ON THEIR ONLINE READING COMPREHENSION AT ENGLISH EDUCATION DEPARTMENT - Mazkhina Berlian Untari; Yahya Alaydrus; Dzurriyyatun Ni'mah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The aim of this study is to know the learners’ perception on their online reading comprehension learning at the English Education Department at the second semester of University of Islam Malang. A qualitative approach research design was used in this study. The participants are 30 students from second semester of English Education Department, class 2A and 2B. The instruments used to collect the data were questionnaire. The questionnaire consisted of 30 statements. Google Form was used to obtain the data and the result was used to analyze the data. As a result of the study, the researcher concluded that the benefits of online reading have had a substantial effect on the knowledge of learners' comprehension, and that students have strongly focused on the educational evaluation they read. The are advantages; the convenience when you understand the text because of the design/facilities, save print paper, transparent screen without bad printing quality, improve online translation, helpful to understand information, important to improve reading skills and the disadvantages; Incapability to leave a mark and make a notation, exhaustion of read many sentences on the light screen, and the distractions.Key Words : Learners’ Perception, Online Learning, Reading Comprehension